The synergistic effect of digital transformation technology and supply chain finance: empirical evidence from 500 listed companies - Liu, Zongtuan; Zhang, Jiajie; Cao, Lei (Frontiers in Physics, 2025)
This paper aims to deeply explore the synergistic effect of digital transformation technology innovation and supply chain finance (SCF) to promote enterprise innovation and enhance competitiveness. Based on the co-evolution theory and economic effect theory, a theoretical framework is constructed to analyze the synergistic effects of SCF and technological innovation. The paper employs the entropy weight-TOPSIS model and the Coupling Coordination Degree model to conduct an in-depth analysis of the synergistic effects from both quantitative and qualitative dimensions. A sample of 500 listed companies from various industries and sizes, covering the period from 2014 to 2021, is selected. By analyzing the financial data and technological innovation indicators of these companies, the relationship and synergistic effects between SCF and technological innovation are investigated. The data analysis results show that starting from 2015, the coupling coordination degree between SCF and technological innovation began to rise rapidly due to fluctuations in the global financial market and the domestic industrial chain transfer. During this period, the coupling coordination degree of the composite system increased significantly from 0.5432 in 2015 to 0.8185 in 2021. This indicates a significant synergistic effect between SCF and technological innovation, with technological innovation playing a leading role in the co-evolution process. This paper reveals the dominant role of technological innovation in the co-evolution process, providing important insights for enterprise development and innovation.